2015
DOI: 10.1186/s12977-015-0153-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrase inhibitor reversal dynamics indicate unintegrated HIV-1 dna initiate de novo integration

Abstract: BackgroundGenomic integration, an obligate step in the HIV-1 replication cycle, is blocked by the integrase inhibitor raltegravir. A consequence is an excess of unintegrated viral DNA genomes, which undergo intramolecular ligation and accumulate as 2-LTR circles. These circularized genomes are also reliably observed in vivo in the absence of antiviral therapy and they persist in non-dividing cells. However, they have long been considered as dead-end products that are not precursors to integration and further v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 32 publications
6
43
0
Order By: Relevance
“…ϩ T cells (58)(59)(60)(61). To exclude the possibility that some forms of this unintegrated HIV-1 DNA become integrated upon T cell activation, resulting in productive infection and virus particle production, we next assessed the contribution of unintegrated HIV-1 LAI DNA to extracellular vRNA production from both T N and T CM cells by including the integrase inhibitor raltegravir (RAL) at the same time as anti-CD3/CD28 (Fig.…”
Section: Resting Cd4mentioning
confidence: 99%
“…ϩ T cells (58)(59)(60)(61). To exclude the possibility that some forms of this unintegrated HIV-1 DNA become integrated upon T cell activation, resulting in productive infection and virus particle production, we next assessed the contribution of unintegrated HIV-1 LAI DNA to extracellular vRNA production from both T N and T CM cells by including the integrase inhibitor raltegravir (RAL) at the same time as anti-CD3/CD28 (Fig.…”
Section: Resting Cd4mentioning
confidence: 99%
“…Interestingly, RNA transcription from unintegrated HIV DNA circles has been reported1516171819. It has been shown that episomal HIV DNA can lead to the production of HIV proteins and may even generate fully replication competent viruses202122. However, the implications of transcription from 2-LTR circles, especially in the context of HIV latency, have remained underestimated and incompletely understood1923.…”
mentioning
confidence: 99%
“…However, this is based on the assumption that unintegrated HIV DNA forms do not contribute to the production of viral transcription and protein production. It is already well known that 2-LTRs accumulate in the presence of INSTI in active infection as well as in treatment intensifications studies in vivo 1720212425.…”
mentioning
confidence: 99%
“…However, Thierry et al recently provided new insight into the role of 2-LTRs for the viral replication cycle; where accumulated 2-LTR forms by RAL treatment in vitro could be converted to linear forms by RAL withdrawal, which were then integrated (Thierry et al, 2015). Although our observations that accumulation of cHIV DNAs by INSTIs were especially emphasized under cell-to-cell transmission, they suggest a cryptic role for unintegrated cHIV DNA in viral replication.…”
Section: Discussionmentioning
confidence: 59%